Accidental Chronic Poisoning with Methotrexate; Report of Two Cases - Bidaki, Reza; Kian, Mojgan; Owliaey, Hamid; Babaei Zarch, Mojtaba; Feysal, Masoud (Archives of Academic Emergency Medicine, 2017)
Methotrexate has been used widely in dermatology, oncology and rheumatology fields. However, methotrexate-induced mucocutaneous lesions may occur in rare cases. In this case presentation, we report two cases of accidental poisoning with methotrexate. They had accidentally used methotrexate instead of digoxin. This case report emphasizes that early diagnosis and appropriate management is critical in order to improve outcome.